International regime complexes and corporate crime: a research agenda based on the Volkswagen diesel fraud case - Braun, Caelesta (Crime, law and social change, 2022)
Criminological literature has often pointed to the absence or weakness of existing international regulation as important explanatory factors of corporate crime in global markets. This paper addresses the presence of multiple parallel, nested and overlapping regulatory regimes, and explores how such international regime complexity creates pathways to corporate crime. We use the Volkswagen diesel fraud case as a plausibility probe to illustrate such pathways to corporate crime. Our tentative analysis suggests that Volkswagen’s fraud in the US cannot be seen as independent of the EU regulatory regime, which was more lenient and offered various opportunities for creative compliance. We conclude that a regime complexity perspective is a promising addition to existing explanations of corporate crime in international settings and suggest a research agenda for future in-depth analyses of the implications of parallel and conflicting regulatory regimes for corporate crime.